2015
DOI: 10.1177/1321103x15609800
|View full text |Cite
|
Sign up to set email alerts
|

Informal music education: The nature of a young child’s engagement in an individual piano lesson setting

Abstract: The purpose of this study was to gain insight into the nature of a young child's engagement in an individual music lesson setting based on principles of informal learning. The informal educational space allowed the child to observe, explore, and interact with a musical environment as a process of enculturation and development (Gordon, 2013;McCloskey, 2012). The setting incorporated the piano, and was considered a readiness experience for later formal piano training. Data collection occurred via video recording… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…e piano's key tone is formulated in accordance with the "twelve equal temperament." e production materials of piano strings are different, and the pronunciation is different [9]. From the overall structure, the piano is composed of three parts: shell, machinery and sound source.…”
Section: Overview Of the Pianomentioning
confidence: 99%
“…e piano's key tone is formulated in accordance with the "twelve equal temperament." e production materials of piano strings are different, and the pronunciation is different [9]. From the overall structure, the piano is composed of three parts: shell, machinery and sound source.…”
Section: Overview Of the Pianomentioning
confidence: 99%
“…Recent studies (e.g., Barrett, 2011; Kooistra, 2016; Young, 2005) that have considered the nature and role of musical communication in music-making and musical experience show that young children are inherently creative and willingly interact with music. They can communicate naturally with sounds, seeking understanding of music, when they are expected and encouraged.…”
Section: Nonverbal Musical Communicationmentioning
confidence: 99%
“…The small amount time to get elsewhere and to set up and organize within small groups changes the pace, briefly requires full body engagement, and contributes to collaboration and problem solving. Breaking up the large ensemble by encouraging both like and unalike groupings to practice at various spaces within the room not only involves the act of moving, getting students out of the chairs, but it also adds to the students' autonomy over how and where they engage in their student-led practice (Kooistra, 2016).…”
Section: Physical Movementmentioning
confidence: 99%
“…Although the author has not polled his colleagues, he believes many of them would say they facilitate these actions within their large ensembles seated in standard formats. However, the large ensemble is not the only means of teaching and learning, and in some scholarly writing, it is now suggested that the focus of large ensemble instruction is detrimental to individual musicianship and growth, hence to the music education profession (Kooistra, 2016;Mantie, 2012). This article is not going to defend or deny such position.…”
Section: Paraxial Music Educationmentioning
confidence: 99%